Conceptual Foundations of Women's Issues in Uzbekistan (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The conceptual framework of women's issues in Uzbekistan is based on the principles of gender equality, women's rights and social justice. State policy on this issue is aimed at increasing the economic, social and political activity of women, creating equal opportunities in education and the labor market. Women's rights are protected on the basis of the Constitution of the Republic of Uzbekistan and international obligations, in particular, the UN documents on Gender Equality. In recent years, significant steps have been taken to eliminate gender stereotypes, combat domestic violence and support women's entrepreneurial activities. However, socio-cultural traditions and economic restrictions remain obstacles to achieving equality in some areas. The coherence of state programs and the activities of civil society organizations on this issue is important. In the future, an integrated approach is required to further strengthen women's rights and increase their role in society.